Outcome of twin deliveries according to planned mode of delivery at Level II hospitals within the Metro West Cape Town Health District - Schroeder, Amaal (Department of Obstetrics and Gynaecology, 2019)
Twin pregnancies are associated with greater fetal and neonatal morbidity and mortality compared to singleton pregnancies. It has been shown in a large multicentre randomised control trial by Barrett et al, that this risk is not significantly changed by planned mode of delivery in a twin pregnancy with a cephalic presenting first twin. This study was undertaken to assess the outcome of cephalic-presenting twin gestations according to planned mode of delivery in the local context of secondary level hospitals in the Metro West Cape Town Health District. Methods: This was a retrospective cohort study of twin deliveries at Mowbray Maternity Hospital and New Somerset Hospital over a 12 month period, starting from 1 January 2013 until the 31 December 2013. Study subjects included all twin deliveries with a cephalic presenting first twin, gestational age > 28w and 0 days, with no contraindication to vaginal delivery. The primary outcome was to document fetal and neonatal outcome according to the planned mode of delivery. Secondary outcomes included maternal outcomes and associations for combined delivery. Result: A total of 124 cases were identified. 95 had a planned vaginal delivery, and 29 had a planned caesarean section. In the planned vaginal delivery group, 61.1% delivered vaginally and 38.9% delivered via caesarean section. Nine of these caesarean sections were combined deliveries. The planned caesarean section group had a caesarean section rate of 93.1%. Two cases delivered vaginally. There was no statistical difference in the composite neonatal score between the two groups (21.1% and 29.3%, in the planned vaginal delivery and planned caesarean section groups respectively, p=0.092). There was also no significant differences in maternal outcomes between the two groups. Conclusion: The results of this study are in keeping with the findings of the Twin Birth Study. It showed no statistically significant difference in neonatal and maternal outcomes of twin gestations, with a cephalic presenting first twin, with respect to planned mode of delivery. A trial of vaginal birth is therefore a feasible option in our setting.